Atributos físicos de latossolo vermelho sob pousio ou cultivado com forrageiras tropicais sob pastejo - Castagnara, Deise Dalazen; Karwatte Júnior, Nivaldo; Zoz, Tiago [UNESP]; Piano, Jéferson Tiago; Rossol, Charles Douglas; de Oliveira, Paulo Sérgio Rabello; Seidel, Edleusa Pereira (My University, 2012)
The objective was to study the physical attributes of an Oxisol under fallow or planted with tropical grasses under grazing. The experiment was conducted under the experimental design of randomized blocks in split-plot 2 × 5, being five types of use of soil (Brachiaria ruziziensis, Panicum maximum cv. Aries, Brachiaria brizantha cv. MG5, Panicum maximum cv. Mombaça and fallow) and two evaluation periods (after the first and after the second grazing), with four replications. We evaluated the characteristics of soil bulk density, total porosity, microporosity and macroporosity, after the first and second grazing, and soil resistance to penetration after the second grazing. In layer of 0.00 to 0.10 m, the macroporosity was affected by the interaction between types of use and evaluation periods, while the microporosity and total porosity were reduced and the density was increased from first to second evaluation time. In the subsurface layer (0.10-0.20 m), there were significant effect only of evaluation time, on the macroporosity, total porosity and density. The porosity were reduced, while the density increased from first to second evaluation time. No significant effects of types of use of soil on penetration resistance in all layers studied. The maintenance of an Oxisol under fallow or cultivation with tropical grasses subjected to grazing cattle causes a reduction in total porosity and increased density of surface soil layers (0 to 0.10 m) and subsurface (0.10 - 0.20 m), without promoting changes on resistance to penetration mechanics.
Physical attributes of Oxisol under fallow or cultivated with tropical forages under grazing
Keywords: Porosity; Resistance to penetration; Soil bulk density